Activity and Stability of Platinum Reforming Catalysts.Computer Evaluation and Prediction; Chemistry and Technology of Fuels and Oils; Vol. 40, iss. 3 - Kravtsov A. V. Anatoly Vasilyevich; Ivanchina E. D. Emilia Dmitrievna; Averin S. N.; Fedorov A. A.; Krupenya L. V.; Poluboyartsev D. S. (2004, 2004)
Title screen